A repairing method of copper-aluminum composite bus and copper-aluminum repairing composite bus

By depositing a repair layer on copper-aluminum composite busbars using cold spraying technology, optimizing process parameters, and using pure copper powder, the failure problem caused by inconsistent contact resistance and thermal expansion coefficient of copper-aluminum composite busbars was solved, achieving efficient and high-performance repair, extending service life, and saving resources.

CN116598944BActive Publication Date: 2026-11-06GUANGDONG INST OF NEW MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310692996.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2026-11-06
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

In practical applications, copper-aluminum composite bars fail due to high contact resistance and inconsistent coefficients of thermal expansion, making it difficult to achieve efficient and high-performance repair using traditional methods.

Method used

Cold spraying technology is used to deposit a repair layer on the area to be repaired of the copper-aluminum composite busbar. Process parameters such as working gas pressure, temperature, spraying distance, spray gun moving speed and powder feeding rate are optimized. Pure copper powder is used as the spraying raw material, and surface cleaning, roughening treatment and post-machining treatment are performed.

Benefits of technology

A dense and highly bonded repair layer is obtained, with superior electrical conductivity, average hardness, and thermal conductivity compared to the original composite busbar, extending the service life of the copper-aluminum composite busbar and saving resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116598944B_ABST
    Figure CN116598944B_ABST
Patent Text Reader

Abstract

This invention discloses a repair method for copper-aluminum composite busbars and a repaired copper-aluminum composite busbar, belonging to the field of conductor material technology. The repair method includes the following steps: depositing a repair layer on the area to be repaired of the copper-aluminum composite busbar using a cold spray method; the cold spray process conditions include: working gas pressure of 1-10 MPa; working gas temperature of 100-1000℃; spraying distance of 10-100 mm; spray gun moving speed of 10-1000 mm / s; and powder feeding rate of 1-500 g / min. This method can effectively repair scrapped copper-aluminum composite busbars, extend their service life, achieve economic and resource conservation, and has significant application value. In the resulting repaired copper-aluminum composite busbar, the performance of the repair layer is higher than that of the copper layer in the original copper-aluminum composite busbar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductor materials technology, and more specifically, to a method for repairing copper-aluminum composite busbars and a method for repairing copper-aluminum composite busbars. Background Technology

[0002] Copper-aluminum composite busbars, commonly known as copper-clad aluminum busbars or copper-clad aluminum busbars, were first proposed in 2012. One of their significances is the reduction of copper consumption. By strongly encouraging manufacturers to develop new copper-aluminum composite materials, copper consumption can be reduced, achieving the goal of "saving copper with aluminum." Furthermore, since copper is much more expensive than aluminum, another significant benefit is reducing material costs for enterprises.

[0003] Despite the promising future of copper-aluminum composite busbars, practical applications often encounter challenges such as high contact resistance leading to material burn-out and inconsistent thermal expansion coefficients causing copper layer detachment, resulting in material failure. Traditional manufacturing methods for copper-aluminum composite busbars include cladding welding, hydrostatic extrusion, and multilayer electroplating. Unlike copper and aluminum busbars, copper-aluminum composite busbars are difficult to recycle.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] One of the objectives of this invention is to provide a method for repairing copper-aluminum composite busbars to solve the aforementioned technical problems.

[0006] The second objective of this invention is to provide a copper-aluminum repaired composite busbar obtained by the above-mentioned repair method.

[0007] This application can be implemented as follows: In a first aspect, this application provides a method for repairing copper-aluminum composite busbars, which includes the following steps: A repair layer is deposited on the area to be repaired of the copper-aluminum composite busbar using a cold spraying method. The process conditions for cold spraying include: working gas pressure of 1-10MPa; working gas temperature of 100-1000℃; spraying distance of 10-100mm; spray gun moving speed of 10-1000mm / s; and powder feeding rate of 1-500g / min.

[0008] In an optional embodiment, the process conditions for cold spraying include: working gas pressure of 3-8 MPa; working gas temperature of 300-800℃; spraying distance of 30-80 mm; spray gun moving speed of 100-500 mm / s; and powder feeding rate of 20-200 g / min.

[0009] In an optional implementation, the working gas includes at least one of air, nitrogen, and helium.

[0010] In an optional embodiment, the spraying material used for the repair layer is copper powder with an average particle size of 10-100 μm and a copper content of ≥95 wt%.

[0011] In an optional embodiment, the copper powder is pure copper powder and / or copper powder.

[0012] In an optional implementation, before depositing the repair layer, the surface of the area to be repaired is further cleaned and roughened.

[0013] In an optional embodiment, the cleaning agent used for surface cleaning includes anhydrous alcohol or acetone; Alternatively, the surface roughening process may involve grinding with a grinding wheel, sanding with sandpaper, or sandblasting.

[0014] In an optional implementation, after depositing the repair layer, the repair layer is further subjected to a machining post-processing.

[0015] In an optional implementation, post-machining treatments include turning, grinding, and / or polishing.

[0016] Secondly, this application provides a copper-aluminum repairable composite busbar, which is obtained by repairing the copper-aluminum composite busbar to be repaired through any of the repair methods described in the foregoing embodiments.

[0017] In an optional embodiment, the copper-aluminum repair composite busbar includes at least one of the following features: Feature 1: The copper-aluminum composite busbar has a pure copper-clad pure aluminum structure; Feature 2: The thickness of the repair layer is ≥20μm; Feature 3: The bonding strength between the repair layer and the surface of the area to be repaired is ≥50MPa; Feature 4: The density of the repair layer is ≥95%; Feature 5: The electrical conductivity of the repair layer is ≥90% IACS; Feature 6: The average hardness of the repair layer is ≥120HV 0.3 ; Feature 7: The thermal conductivity of the repair layer is ≥375W / (m·K).

[0018] The beneficial effects of this application include: This application creatively proposes a method of cold spraying and optimized process parameters to achieve efficient and high-performance repair of copper-aluminum composite busbars. The resulting repair layer is dense and has high bonding strength. Its electrical conductivity, average hardness, and thermal conductivity are superior to those of the original copper layer of the composite busbar, thereby extending the service life of the copper-aluminum composite busbar, saving resources, and having high application value. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 A schematic diagram of the cold spraying equipment used in the repair method for the copper-aluminum composite busbar provided in this application; Figure 2 This is a sample image of the copper-aluminum composite busbar before repair in Example 1. The image shows the upper surface of the sample. Figure 3 This is a sample image of the copper-aluminum composite busbar after repair in Example 1. The image shows the upper surface of the sample. Figure 4 This is a sample image of the copper-aluminum composite busbar after repair in Example 1. The image shows the side of the sample after polishing. Figure 5 This is a metallographic image of the repair layer in Example 1. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0022] The following provides a detailed explanation of the repair method for the copper-aluminum composite busbar provided in this application and the copper-aluminum repair method for the composite busbar.

[0023] The inventors proposed that, given the difficulty in recycling copper-aluminum composite bars, various methods (such as thermal spraying, laser welding, or resin patching) have been attempted to repair areas of the copper-aluminum composite bars that have suffered burns or detachment. However, none of these methods have been able to achieve efficient and high-performance repair. This may be because copper and aluminum have significant differences in physical properties, such as their coefficients of thermal expansion and melting points. Using a melting-solidification-based preparation process can easily lead to problems such as localized burns and coating detachment.

[0024] Through continuous experimentation and exploration, the inventors have creatively proposed a method for efficiently and effectively repairing the failed areas of copper-aluminum composite busbars, thereby meeting increasingly demanding service conditions and improving the service life of copper-aluminum composite busbars.

[0025] Specifically, the repair method for the copper-aluminum composite busbar includes the following steps: depositing a repair layer on the area to be repaired of the copper-aluminum composite busbar using a cold spraying method.

[0026] The aforementioned copper-aluminum composite busbar has a pure copper-clad pure aluminum structure.

[0027] In this application, the process conditions for cold spraying may include: working gas pressure of 1-10 MPa; working gas temperature of 100-1000℃; spraying distance of 10-100 mm; spray gun moving speed of 10-1000 mm / s; and powder feeding rate of 1-500 g / min.

[0028] For reference, the pressure of the working gas can be 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, 5 MPa, 5.5 MPa, 6 MPa, 6.5 MPa, 7 MPa, 7.5 MPa, 8 MPa, 8.5 MPa, 9 MPa, 9.5 MPa or 10 MPa, or any other value in the range of 1-10 MPa, preferably 3-8 MPa.

[0029] If the working air pressure is less than 1 MPa, it is easy to cause ineffective spraying and deposition; if the working air pressure is greater than 10 MPa, it is easy to cause damage to the reliability of the equipment.

[0030] The temperature of the working gas can be 100℃, 150℃, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 505℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃ or 1000℃, or any other value within the range of 100-1000℃, preferably 300-800℃.

[0031] If the temperature of the working gas is below 100℃, it may lead to ineffective spraying and deposition; if the temperature of the working gas exceeds 1000℃, it may lead to damage to the reliability of the equipment.

[0032] The working gas may include, for example, at least one of air, nitrogen, and helium.

[0033] During spraying, the spraying distance can be 10mm, 20mm, 30mm, 40mm, 50mm, 60mm, 70mm, 80mm, 90mm or 100mm, or any other value within the range of 10-100mm, preferably 30-80mm.

[0034] If the spraying distance is less than 10mm, it is easy to cause the spray gun to collide; if the spraying distance is greater than 100mm, it is easy to cause ineffective spraying and deposition.

[0035] The moving speed of the spray gun can be 10mm / s, 50mm / s, 100mm / s, 200mm / s, 300mm / s, 400mm / s, 500mm / s, 600mm / s, 700mm / s, 800mm / s, 900mm / s or 1000mm / s, or any other value in the range of 10-1000mm / s, preferably 100-500mm / s.

[0036] If the spray gun moves at a speed less than 10 mm / s, it can easily lead to excessive local heat accumulation and material oxidation and detachment; if the spray gun moves at a speed greater than 1000 mm / s, it exceeds the upper limit of the robot arm's stable operation.

[0037] The powder feeding rate can be 1 g / min, 5 g / min, 10 g / min, 50 g / min, 100 g / min, 150 g / min, 200 g / min, 250 g / min, 300 g / min, 350 g / min, 400 g / min, 450 g / min or 500 g / min, or any other value in the range of 1-500 g / min, preferably 20-200 g / min.

[0038] If the powder feeding rate is less than 1 g / min, it is easy to cause ineffective and unstable powder feeding; if the powder feeding rate is greater than 500 g / min, it is easy to cause overload of the spraying gas, resulting in a decrease in spraying efficiency.

[0039] It should be noted that the equipment used for the above-mentioned spraying (such as...) Figure 1 As shown in the figure, the spraying principle can be referred to in relevant existing technologies, and will not be elaborated on here.

[0040] In this application, the spraying material used for the repair layer is copper powder, such as pure copper powder and / or red copper powder.

[0041] For reference, the average particle size of the copper powder used can be 10-100 μm, and it can be spherical or irregular in shape.

[0042] If the average particle size of the copper powder is less than 10 μm, it is not conducive to stable powder feeding by the powder feeder; if the average particle size of the copper powder is greater than 100 μm, it is not conducive to effective deposition of cold spray coating.

[0043] For reference, the copper powder used has a copper content of ≥95wt%, which can achieve better repair performance.

[0044] In this application, before depositing the repair layer, the surface of the area to be repaired is cleaned and roughened, and non-sprayed areas are clamped and shielded using tooling.

[0045] For reference, cleaning agents used for surface cleaning may include, for example, anhydrous alcohol or acetone.

[0046] Surface roughening treatments may include, for example, grinding with a grinding wheel, sanding with sandpaper, or sandblasting.

[0047] Furthermore, after depositing the repair layer, the process also includes machining the repair layer.

[0048] For reference, post-machining treatments may include turning, grinding, and / or polishing to restore the original dimensions and surface condition.

[0049] Accordingly, this application also provides a copper-aluminum repaired composite busbar, which is obtained by repairing the copper-aluminum composite busbar to be repaired using the above-mentioned repair method.

[0050] For reference, the thickness of the repair layer of the obtained copper-aluminum repair composite strip is ≥20μm, such as 20μm, 50μm, 100μm, 200μm, 500μm, 800μm or 1000μm, etc.

[0051] The bonding strength between the repair layer and the surface of the area to be repaired is ≥50MPa, and in some embodiments it can reach 115MPa.

[0052] The density of the repair layer is ≥95%, and in some embodiments it can reach 99%.

[0053] The electrical conductivity of the repair layer is ≥90% IACS, and in some embodiments it can reach 95% IACS.

[0054] The average hardness of the repair layer is ≥120 HV. 0.3 In some implementations, it can reach 153 HV. 0.3 .

[0055] The thermal conductivity of the repair layer is ≥375W / (m·K), and in some embodiments it can reach 400W / (m·K).

[0056] As described above, the method provided in this application can obtain a dense repair layer with high bonding strength. Moreover, the electrical conductivity, average hardness, and thermal conductivity of this repair layer are superior to those of the original composite busbar. This enables effective repair of scrapped copper-aluminum composite busbars, extends their service life, saves resources, and has high application value.

[0057] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0058] Example 1 This embodiment provides a method for repairing copper-aluminum composite busbars, which includes: (1) The area to be repaired for the copper-aluminum composite busbar (e.g.) Figure 2 (As shown) The surface of the area to be repaired is subjected to degreasing, cleaning and polishing; after polishing, the surface roughness Ra of the area to be repaired is ≤10μm.

[0059] (2) Using cold spraying technology, pure copper powder is deposited on the surface of the copper-clad aluminum busbar to be repaired by optimizing the spraying trajectory and spraying parameters.

[0060] In this process, nitrogen gas was used at a pressure of 5 MPa and a temperature of 800℃. The spraying distance was 40 mm, the spray gun moving speed was 400 mm / s, and the powder feeding rate was 100 g / min. The particles to be sprayed were spherical pure copper powder with an average particle size of 45 μm and a copper content ≥99.9 wt.%. The thickness of the deposited layer after deposition was 650 μm.

[0061] (3) The surface coating of the repaired component is processed by turning, grinding, polishing, etc., to restore its original size and surface condition, and the repaired copper-aluminum composite busbar (e.g.) is obtained. Figure 3 and Figure 4 (As shown).

[0062] Metallographic image of the repair layer as follows Figure 5 As shown, by Figure 5 It can be seen that the repair layer has a uniform and dense structure, without cracks or defects.

[0063] Example 2 The difference between this embodiment and Embodiment 1 is that: In step (1), the surface is treated with sandblasting, and the surface roughness Ra of the area to be repaired after pretreatment is ≤5μm.

[0064] In step (2), the working gas is helium, the working gas pressure is 3 MPa, the working gas temperature is 300℃, the spraying distance is 30 mm, the spray gun moving speed is 100 mm / s, and the powder feeding rate is 95 g / min. The particles to be sprayed are spherical pure copper powder with an average particle size of 30 μm and a copper content ≥99.9 wt.%. The thickness of the deposited layer after deposition is 300 μm.

[0065] Example 3 The difference between this embodiment and Embodiment 1 is that: In step (1), the surface is treated with sandblasting, and the surface roughness Ra of the area to be repaired after pretreatment is ≤5μm.

[0066] In step (2), the working gas is helium, the working gas pressure is 3 MPa, the working gas temperature is 300℃, the spraying distance is 30 mm, the spray gun moving speed is 500 mm / s, and the powder feeding rate is 115 g / min. The particles to be sprayed are irregularly shaped copper powder with an average particle size of 25 μm and a copper content ≥99.7 wt.%. The thickness of the deposited layer after deposition is 450 μm.

[0067] Example 4 The difference between this embodiment and Embodiment 1 is that: The working gas used is nitrogen, with a working gas pressure of 8MPa, a working gas temperature of 500℃, a spraying distance of 30mm, a spray gun moving speed of 300mm / s, and a powder feeding rate of 20g / min.

[0068] Example 5 The difference between this embodiment and Embodiment 1 is that: The working gas used is nitrogen, with a working gas pressure of 6MPa, a working gas temperature of 700℃, a spraying distance of 10mm, a spray gun moving speed of 10mm / s, and a powder feeding rate of 10g / min.

[0069] Example 6 The difference between this embodiment and Embodiment 1 is that: The working gas used is nitrogen, with a working gas pressure of 4MPa, a working gas temperature of 1000℃, a spraying distance of 100mm, a spray gun moving speed of 800mm / s, and a powder feeding rate of 400g / min.

[0070] Comparative Example 1 The difference between this comparative example and Example 1 is that a pure copper repair layer is deposited using a thermal spraying method.

[0071] The thermal spraying process parameters are as follows: spraying distance from the substrate surface is 120mm, spraying angle is approximately 90°, powder delivery gas flow rate is 50L / min, Ar gas flow rate is 60L / min, and operating current is 400A.

[0072] Comparative Example 2 The difference between this comparative example and Example 1 is that a pure copper repair layer is deposited using laser welding.

[0073] The laser welding process parameters are: laser power 1200W, laser focal length 30mm, and welding speed 60mm / s.

[0074] Test case Using the original copper layer of the copper-aluminum composite busbar to be repaired as a control, the repair layers obtained in Examples 1-6 and Comparative Examples 1-12 were subjected to the following performance tests, and the results are shown in Table 1. The porosity was measured according to GB / T 3489-2015, the bonding strength according to GB / T 8642-2002, the hardness according to GB / T 4340.1-2009, the electrical conductivity according to GB / T 32791-2016, and the thermal conductivity according to GB / T 3651-2008.

[0075] Table 1 Test Results

[0076] As can be seen from Table 1, compared with the comparative example, the repair layer prepared in the embodiments of this application has better density, bonding strength, hardness, electrical conductivity and thermal conductivity than the original copper layer, and the effect of Example 2 is the best.

[0077] In summary, the method provided in this application can obtain a dense repair layer with high bonding strength. Moreover, the repair layer has better electrical conductivity, average hardness, and thermal conductivity than the original composite busbar, thereby enabling effective repair of scrapped copper-aluminum composite busbars, extending their service life, saving resources, and having high application value.

[0078] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for repairing a copper-aluminum composite busbar, characterized in that, Includes the following steps: A repair layer is deposited on the area to be repaired of the copper-aluminum composite busbar using a cold spraying method. The process conditions for cold spraying include: working gas pressure of 3-8 MPa; working gas temperature of 300-800℃; spraying distance of 30-80 mm; spray gun moving speed of 100-500 mm / s; and powder feeding rate of 20-200 g / min. The copper-aluminum composite busbar has a pure copper-clad pure aluminum structure; the spraying material used for the repair layer is copper powder, the average particle size of the copper powder is 10-100μm, and the copper content of the copper powder is ≥95wt%.

2. The repair method according to claim 1, characterized in that, The working gas includes at least one of air, nitrogen, and helium.

3. The repair method according to claim 1, characterized in that, The copper powder is pure copper powder.

4. The repair method according to claim 1, characterized in that, Before depositing the repair layer, the surface of the area to be repaired is also cleaned and roughened.

5. The repair method according to claim 4, characterized in that, The cleaning agents used for surface cleaning include anhydrous alcohol or acetone; Alternatively, the surface roughening process may involve grinding with a grinding wheel, sanding with sandpaper, or sandblasting.

6. The repair method according to claim 1, characterized in that, Following the deposition of the repair layer, the process also includes machining the repair layer.

7. The repair method according to claim 6, characterized in that, Post-machining treatments include turning, grinding, and / or polishing.

8. A copper-aluminum repair composite strip, characterized in that, It is obtained by repairing the copper-aluminum composite busbar to be repaired using the repair method described in any one of claims 1-7.

9. The copper-aluminum repair composite strip according to claim 8, characterized in that, The copper-aluminum repair composite busbar includes at least one of the following characteristics: Feature 1: The thickness of the repair layer is ≥20μm; Feature 2: The bonding strength between the repair layer and the surface of the area to be repaired is ≥50MPa; Feature 3: The density of the repair layer is ≥95%; Feature 4: The electrical conductivity of the repair layer is ≥90% IACS; Feature 5: The average hardness of the repair layer is ≥120HV 0.3 ; Feature 6: The thermal conductivity of the repair layer is ≥375W / (m·K).

Citation Information

Patent Citations

  • Supersonic laser deposition micro shot peening method and spraying device

    CN114250459A